Bats (Mammalia: Chiroptera) in urban fragments of Maringá, Paraná, Brazil - Gazarini, Janaina; Pedro, Wagner André [UNESP] (My University, 2013)
Bat assemblages in two urban fragments of Maringá city, north of the state of Paraná, southern Brazil, were inventoried. These fragments, Parque do Ingá (48 ha) and Parque Florestal dos Pioneiros (59 ha), are located in a subtropical region covered by semideciduous Atlantic forest. Bats were sampled with mist-nets from August 2006 to July 2007, over 24 nights (12 hours a night), adding up to a total of 30,240 h.m2 of net effort. A total of 839 individuals were captured belonging to 10 species and four families. Artibeus lituratus was the most abundant species (66% of the sample). The observed richness represents 22% of the bat species recorded for the state, 24% of the bat species occurring in the seasonal semideciduous forest of Paraná, 26% of the species previously recorded in urban environments in Brazil, and 83.4% of the estimated richness by Jackknife 1 (n= 12 species). Studies that provide data on richness and abundance of bat species in urban fragments are becoming increasingly important, but are still poorly available in Brazil. This habitat is especially interesting because anthropogenic pressure can be harmful to bat assemblages, reducing their diversity. © 2013 Check List and Authors.